Catalogue of Ampulicidae, Crabronidae and Sphecidae of Iran (Hymenoptera, Apoidea) - Jahantigh, Fatemeh; Rakhshani, Ehsan; Mokhtari, Azizollah; Ramroodi, Sara (Zootaxa, 2017)
An updated checklist of the Sphecidae sensu lato (Ampulicidae, Crabronidae and Sphecidae) of Iran is presented. Records were extracted from the literature published between 1871 and 2016. In total, 404 species belonging to 71 genera and 11 subfamilies are listed. While Crabronidae and Sphecidae are represented by 315 (6 subfamilies, 56 genera) and 87 species (4 subfamilies, 13 genera), respectively, only two species belonging to the genera Ampulex Jurine, 1807 and Trirogma Westwood, 1841 from the family Ampulicidae were recorded from Iran. Two species, Bembecinus escalerae (Turner, 1912b) and Tachytes panzeri(Dufour, 1841), are excluded from the sphecid wasp fauna of the country. Among the listed taxa, 18 species are exclusively known from Iran. Also listed are 54 subspecies belonging to 47 species. For each species, recorded distribution in Iran as well as overall distribution is presented. The majority of species were recorded from Fars (140) followed by Sistan-o Baluchestan (103) and Tehran (63) provinces. Printed copy of this book is available from US31.2 plus postage, Click here to order.